Prediction Model of Box Office Based on Arbitrage Pricing Theory: An Empirical Analysis from China - Qingshi, Wang; Naiqian, Li; Ali, Hashmat (International Journal of Economics and Financial Issues, 2019)
According to characteristics of revenue and risks involved in film investments, this paper expounds that movies can also be treated as a common tradable asset in capital markets. Consequently, this study employs the famous Arbitrage Pricing Theory (APT) from Capital Asset Pricing Model as a necessary and efficient theoretical explanation, in order to describe the application of multi-factor linear regression model used in assessing movie investment returns in real life. Above that, the paper not only uses Linear Regression with Multiple Variables and its theory by Litman and Kohl (1989) for reference, but also build a model for explanation and prediction about Chinese movie box office combined with the research experience in predicting movie box office at home and abroad. 219 movies released in Mainland China from 2008 to 2017 were selected as samples for empirical testing and analysis. According to the empirical model, this study predicted the 4 movies released in 2018, satisfactory outcomes were obtained. Keywords: Movie Box Office, Prediction Model, Arbitrage Pricing Theory, Empirical Analysis JEL Classifications: C1 DOI: https://doi.org/10.32479/ijefi.8383